Evaluation of Administration Prophylactic Antibiotic against Incidence of Surgical Site Infection in Post Appendectomy at Panembahan Senopati Hospital, Indonesia - Esa Adzillina; Sri Sundari; Siti Mizabul Ijabah (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Appendicitis is a prevalent abdominal surgical emergency in Indonesia, occurring at a rate of 5 per 1,000 people, with around 10 million cases each year. Appendectomy, the surgical removal of the vermiform, is the primary treatment for appendicitis but carries a high risk of surgical site infections. Prophylactic antibiotics are given to minimize the risk of infection resulting from surgery, administered in accordance with established guidelines. This study aims to evaluate the administration of antibiotic prophylactic against SSIs. This study used a mixed-methods approach to evaluate prophylactic antibiotic administration and the incidence of surgical site infection in post-appendectomy patients. The researchers conducted in-depth interviews with surgeons and nurses and an analytical observational study with a cross-sectional design, observing various indicators such as the timing and duration of prophylactic antibiotic administration and the presence of surgical site infections. The study found that the duration of antibiotic administration ≤24 hours had a higher number of infection-free patients (62.50%). The researchers analyzed the relationship between the duration of antibiotic administration and surgical site infection in post-appendectomy patients and found a significant relationship (p <0.05) at the hospital. There is a relationship between prophylactic antibiotic administration and surgical site infection. All patients were given prophylactic antibiotics with appropriate timing, duration, and method of administration.